c.4 - "Chakravarty, Sukhamoy" (Delhi, 1987)
The book deals with the experience of development planning in India over the last three and a half decades. It explains the analytical considerations which went into the formation of India's development strategy, initially articulated by Nehru and Mahalanobis, and the modifications which were subsequently introduced in the light of experience. It deals with the logical structure of the various Five Year Plans, and the problems of plan implementation. Current debates on economic policy receive an extensive treatment.
Keywords: Economic